Teman Tani: Inclusive Solutions of Integrated Micro Insurance Services to Agricultural Sector Indonesia - Putri, Belinda Azzahra Irwan (Universitas Muhammadiyah Yogyakarta, 2020)
The agricultural sector is one of the main motors that driving the economy of a country, especially for developing country. The development and improvement of the sector is an integral part of national development goals that have a significant and comprehensive impact. However, the risk of business uncertainty in agriculture field such as crop failure due to natural disasters and pest attacks also poses a threat to business continuity. Thus, the existence of financial instruments such as agricultural insurance is the right solution to minimize economic losses from these risks. Unfortunately, the existing agricultural insurance system is not yet effective enough in providing insurance services that are fast, easy and inclusive for farmers. Seeing these problems, it’s needed to propose policy recommendations, namely Teman Tani, as an improvement to the more integrated Rice Farm Business Insurance (AUTP) system for the agricultural sector in Indonesia, especially for the region whose have specialty in it. For research design and data collection, Teman Tani used secondary data searching method from available data such as from BAPPENAS, Agricultural ministry, and Indonesia Financial Services Authority (OJK). After that, the data was analysed using descriptive-qualitative method for system analysis, and inductive method for summarizing, In this system, Insurance Companies will conduct branchless insurance through the OJK Laku Pandai program involving agents to expand insurance coverage to farmers. Then, the process of determining the amount of premiums and submitting claims will be made faster and on target through a decentralized data-exchange process involving collaboration with the DataBot Hara Application. In the process of payment and withdrawal of insurance funds, cooperation with commercial banks and telecommunications companies will be carried out to facilitate farmers through the mobile banking system. Therefore, the Teman Tani program can protect farmers from the risk of business uncertainty so that they can still produce in the next planting season and the objectives of financial inclusion can be achieved. This output target aligned with the vision’s indicator of Sustainable Development Goals number 8, Universal access to banking, insurance and financial services (8.10) and Improve resource efficiency in consumption and production (8.4). In result, Teman Tani can increase the guarantee level of farmer’s agricultural output until 12% and enhance financial inclusivity among the rural society.